2017
DOI: 10.3892/ol.2017.6949
|View full text |Cite
|
Sign up to set email alerts
|

PAX8 is a potential marker for the diagnosis of primary epithelial ovarian cancer

Abstract: The present study aimed to investigate the clinical significance of paired-box 8 (PAX8) in primary epithelial ovarian cancer (PEOC). Using immunohistochemical (IHC) staining, the expression of PAX8 in 60 patients with PEOC, 20 patients with ovarian benign lesions and 10 patients with metastatic ovarian cancer (MOC), was examined based on the clinicopathological profiles of the patients. The correlation between PAX8 expression and the clinicopathological parameters or prognosis of patients was statistically ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
0
25
1
Order By: Relevance
“…PAX8 is also a promising prognostic marker for ovarian cancer with a threshold of 3+ staining in ≥51% cells. 64 Although the percentage decrease in H-score during the DTF time course was not significant, we observed a reduction in the percentage of 3+ PAX8-stained cells in ovary specimens. Furthermore, although different immunoscoring schemes preclude direct comparisons, the reduction in proportion of 3+ WT1 immunopositive cells we observed after a DTF ≥2 hr may straddle the eligibility criteria (an immunoreactive score [IRS] score of 4-12) for a phase I clinical trial on a WT1 vaccine to prevent ovarian cancer reoccurrence (NCT02737787).…”
Section: Discussioncontrasting
confidence: 61%
“…PAX8 is also a promising prognostic marker for ovarian cancer with a threshold of 3+ staining in ≥51% cells. 64 Although the percentage decrease in H-score during the DTF time course was not significant, we observed a reduction in the percentage of 3+ PAX8-stained cells in ovary specimens. Furthermore, although different immunoscoring schemes preclude direct comparisons, the reduction in proportion of 3+ WT1 immunopositive cells we observed after a DTF ≥2 hr may straddle the eligibility criteria (an immunoreactive score [IRS] score of 4-12) for a phase I clinical trial on a WT1 vaccine to prevent ovarian cancer reoccurrence (NCT02737787).…”
Section: Discussioncontrasting
confidence: 61%
“…PAX8 (a member of paired box PAX gene family) is a positive marker of FTSECs 89 and is elevated in a variety of tumors 90 95 . Our prior findings demonstrated that PAX8 was upregulated following chronic iron exposure 10 ; we now validate this observation and further show that it is epigenetically regulated, also supported by prior literature 59 .…”
Section: Resultsmentioning
confidence: 99%
“…PAX8 is a biomarker for diagnosis of several types of malignant tumors [19,20]. To understand the potential role of PAX8 in the progression of HCC, the expression of PAX8 in HCC and nontumor liver tissues in the Oncomine and TCGA was analyzed.…”
Section: Pax8 Silencing Inhibits the Growth Of Hcc In Vitro And In Vivomentioning
confidence: 99%